The Effect Of Lavender Aromatherapy Inhalation On Anxiety In Infants Post-Dpt Immunization At Puskesmas Rum Balibunga, Tidore - Nurdian S.Bangsa; Retno Dewi Prisusanti (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Infant anxiety following routine immunizations, such as DPT vaccination, can lead to distress, prolonged crying, and negative behavioral responses, affecting both the child and caregivers. Non-pharmacological interventions, including aromatherapy, have been explored to alleviate such anxiety. This study aimed to examine the effect of lavender aromatherapy inhalation on anxiety levels in infants after DPT immunization at Puskesmas Rum Balibunga Tidore. A quasi-experimental design with pre-test and post-test measurements was employed, involving 30 infants aged 2–6 months. Anxiety was assessed using a validated observational scale, focusing on behavioral indicators such as crying duration, facial expressions, and body movements. Lavender essential oil was administered via inhalation for five minutes immediately after immunization. Data were analyzed using paired t-tests to evaluate changes in anxiety scores before and after the intervention. The results demonstrated a significant reduction in infant anxiety following lavender inhalation, with mean scores decreasing from 14.5 ± 2.8 to 9.3 ± 2.1 (p < 0.001). Behavioral indicators, including the frequency and duration of crying, were also markedly reduced, supporting the effectiveness of the intervention. These findings align with prior research indicating that lavender essential oil can modulate the autonomic nervous system, promoting relaxation and reducing stress responses. In conclusion, inhalation of lavender aromatherapy effectively decreases post-immunization anxiety in infants. Incorporating this intervention into routine vaccination procedures at community health centers offers a safe, non-invasive, and culturally acceptable method to improve infant comfort and enhance the overall immunization experience.